2020
DOI: 10.1371/journal.pone.0231633
|View full text |Cite
|
Sign up to set email alerts
|

A modified arginine-depleting enzyme NEI-01 inhibits growth of pancreatic cancer cells

Abstract: Arginine deprivation cancer therapy targets certain types of malignancies with positive result in many studies and clinical trials. NEI-01 was designed as a novel arginine-depleting enzyme comprising an albumin binding domain capable of binding to human serum albumin to lengthen its half-life. In the present work, NEI-01 is shown to bind to serum albumin from various species, including mice, rat and human. Single intraperitoneal administration of NEI-01 to mice reduced plasma arginine to undetectable level for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…NEI-01 is another novel ADI-based drug that selectively depletes arginine in tumor cells to induce metabolic stress and cell death. NEI-01 has greater specificity for cancer cells and a longer half-life due to its albumin-binding domain [ 90 ]. In preclinical studies, NEI-01 showed potent anticancer activity against different types of cancer, including pancreatic cancer and leukemia [ 90 , 91 ].…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%
See 2 more Smart Citations
“…NEI-01 is another novel ADI-based drug that selectively depletes arginine in tumor cells to induce metabolic stress and cell death. NEI-01 has greater specificity for cancer cells and a longer half-life due to its albumin-binding domain [ 90 ]. In preclinical studies, NEI-01 showed potent anticancer activity against different types of cancer, including pancreatic cancer and leukemia [ 90 , 91 ].…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%
“…NEI-01 has greater specificity for cancer cells and a longer half-life due to its albumin-binding domain [ 90 ]. In preclinical studies, NEI-01 showed potent anticancer activity against different types of cancer, including pancreatic cancer and leukemia [ 90 , 91 ]. NEI-01 treatment significantly reduced tumor volume and weight in a human pancreatic mouse xenograft model and demonstrated potent anti-leukemia activities in three different types of mouse models [ 90 , 91 ].…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential in various cellular events such as gene expression, metabolic pathways, cell growth and differentiation, and signaling. 1–3 Most of the complex biochemical processes in the body are regulated by one or more enzymes. Abnormal manifestations of enzyme activities will indicate the health status of the body and can be used as a biomarker for diagnosing diseases.…”
Section: Introductionmentioning
confidence: 99%